2022
DOI: 10.1371/journal.pone.0270261
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor-based analysis of community-acquired pneumonia, healthcare-associated pneumonia and hospital-acquired pneumonia: Microbiological distribution, antibiotic resistance, and clinical outcomes

Abstract: Background Healthcare-associated pneumonia (HCAP) lies in the intersection of community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP). Although HCAP is excluded from the revised HAP guideline, reassessment for HCAP is needed considering its heterogeneous characteristics. Methods The microbiological distribution, antibiotic resistance, and clinical outcomes in CAP, HCAP, and HAP were studied retrospectively. The susceptibility to standard CAP regimens (β-lactams plus macrolide or fluoroquinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We found that patients’ background characteristics such as age; male sex; being underweight; residence in a nursing home or extended care facility; being bedridden; prior admission; immunosuppression; and comorbidities of heart failure, liver failure, and COPD, as well as severity of conditions at admission, including dehydration, respiratory failure, conscious disturbance, and hypotension were significantly associated with 30-day hospital mortality. These factors have been consistently reported in older studies in the late 1990s and in more recent studies [ [25] , [26] , [27] , [28] , [29] ]. Bedsores were further identified as an independent risk factor for mortality.…”
Section: Discussionsupporting
confidence: 65%
“…We found that patients’ background characteristics such as age; male sex; being underweight; residence in a nursing home or extended care facility; being bedridden; prior admission; immunosuppression; and comorbidities of heart failure, liver failure, and COPD, as well as severity of conditions at admission, including dehydration, respiratory failure, conscious disturbance, and hypotension were significantly associated with 30-day hospital mortality. These factors have been consistently reported in older studies in the late 1990s and in more recent studies [ [25] , [26] , [27] , [28] , [29] ]. Bedsores were further identified as an independent risk factor for mortality.…”
Section: Discussionsupporting
confidence: 65%
“…The ever-increasing number of people living with chronic diseases and comorbidities, such as structural lung disease, diabetes, chronic kidney disease and immune suppression has also driven a higher risk for pneumonia caused by Gram-negative, often drug-resistant organisms [17 ▪▪ ,18]. Finally, recent antibiotics, being bed-bound or living in a long-term care facility, also maps to a higher risk for drug-resistant organisms in CAP [19].…”
Section: The Increasing Prevalence Of Gram-negative Bacteria In Low R...mentioning
confidence: 99%
“…The incidence of the different drug-resistant pathogens (DRP) in CAP is variable in different studies, ranging from 3.5% to 45% [141][142][143][144][145][146]. Several factors play a role, such as the year or location of the study, patient profiles, their risk factors, severity at presentation, etc.…”
Section: Cap and Drug-resistant Pathogensmentioning
confidence: 99%
“…Several factors play a role, such as the year or location of the study, patient profiles, their risk factors, severity at presentation, etc. (Table 7) [141][142][143][144][145][146]. The prevalence of DRP-CAP varies according to the region.…”
Section: Cap and Drug-resistant Pathogensmentioning
confidence: 99%
See 1 more Smart Citation